IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (MBS)DALAM PENINGKATAN MUTU PEMBELAJARANPENDIDIKAN AGAMA ISLAM - Tihalimah Tihalimah (Madrasa : Jurnal Ilmu Pendidikan dan Teknologi, 2026)
School-Based Management (SBM) positions the school as the center of decision-making through autonomy, participation, transparency, accountability, and continuous quality improvement. This article analyzes the implementation of SBM in improving the quality of Islamic Religious Education (IRE) learning, particularly in planning, resource organization, instructional practice, partnerships, and evaluation. The study employs a qualitative literature-review approach using legislation, scholarly books, and international reports on educational decentralization and SBM. Data were analyzed through reduction, categorization, source comparison, and conceptual synthesis. The review indicates that SBM may strengthen IRE learning when school authority is translated into programs responsive to student needs; principals support teacher professionalism; school committees and parents participate substantively; and learning outcomes are assessed across knowledge, attitudes, and skills. Its impact is not automatic, but depends on leadership capacity, teacher competence, resource availability, collaborative culture, and accountability mechanisms. A recommended implementation cycle includes needs mapping, participatory planning, contextual instruction, academic supervision, evidence-based evaluation, and continuous follow-up.